2021
DOI: 10.1002/pat.5522
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and mechanical properties of water‐dispersible hyperbranched polymer grafted carbon black/natural rubber composites by latex blending method

Abstract: In order to improve the mechanical properties of rubber-matrix composites, carboxyl-terminated hyperbranched poly (2-hydroxypropane-1,2,3-tricarboxylic acid) grafted carbon black (CB-g-CTHBP) was prepared, and it could be stably dispersed in water for up to 90 days. CB-g-CTHBP dispersion and natural rubber latex were blended to obtain NR/CB-g-CTHBP, and the effect of CB-g-CTHBP content on the mechanical properties of composites was discussed. The results show that the dispersibility and wettability of CB-g-CTH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…The greater molecular weight leads to higher flexibility, which is conducive to improving the elongation at break. The better CB dispersion in the wet‐mixing method than in the dry‐mixing method is responsible for the higher hardness, which has been confirmed in reported work 27 …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The greater molecular weight leads to higher flexibility, which is conducive to improving the elongation at break. The better CB dispersion in the wet‐mixing method than in the dry‐mixing method is responsible for the higher hardness, which has been confirmed in reported work 27 …”
Section: Resultssupporting
confidence: 81%
“…The better CB dispersion in the wet-mixing method than in the dry-mixing method is responsible for the higher hardness, which has been confirmed in reported work. 27 Using the wet mixing method, the tensile strength of the NR/WPRP composites decreases with increasing the WPRP content when using the 80-mesh and 100-mesh WPRPs, while increases and then decreases when using the 120-mesh and 140-mesh WPRPs. The elongation at break generally tends to increase and then decrease.…”
Section: Physical and Mechanical Propertiesmentioning
confidence: 97%
“…Based on the characterization data, the tensile strength and tear strength of the rubber were increased by 6.1 MPa and 19.5 KN/m, respectively and the rubber also achieved higher abrasion resistance. Similar to the PEG modification approach, Han et al [11] attempted to use hyper-branched poly (2hydroxypropane-1,2,3-tricarboxylic acid) (HBP) to conduct this grafting modification. The difference in this modification procedure was that, before grafting the HBP, a pretreatment was conducted where a great number of carboxyl groups were introduced on the carbon black surface.…”
Section: Graft Modification Of Carbon Blackmentioning
confidence: 99%
“…Mei et al 8 reported a way to modify silica via using oleylamine and γ‐(2,3‐epoxypropoxy) propytrimethoxysilane (KH560), and the results demonstrated the lower rolling resistance and better mechanical properties of NR/silica composite were obtained. Others about the hybrid fillers, 9 graft of CB by hyperbranched polymer, 10 polyethylene glycol, 11 and wet masterbatch technology 12 had been mentioned before.…”
Section: Introductionmentioning
confidence: 99%